2014
DOI: 10.1186/2191-219x-4-5
|View full text |Cite
|
Sign up to set email alerts
|

Half-time Tc-99m sestamibi imaging with a direct conversion molecular breast imaging system

Abstract: BackgroundIn an effort to reduce necessary acquisition time to perform molecular breast imaging (MBI), we compared diagnostic performance of MBI performed with standard 10-min-per-view acquisitions and half-time 5-min-per-view acquisitions, with and without wide beam reconstruction (WBR) processing.MethodsEighty-two bilateral, two-view MBI studies were reviewed. Studies were performed with 300 MBq Tc-99 m sestamibi and a direct conversion molecular breast imaging (DC-MBI) system. Acquisitions were 10 min-per-v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Regions of interest were drawn to encompass the breast tissue, excluding the pectoralis muscle, with the average counts per pixel recorded. A reader also provided an overall assessment of diagnostic image quality and noise level as previously described [16] and an assessment of motion artifacts. Image quality was scored using the following 1-5 scale: 1 (poor, non-diagnostic); 2 (suboptimal, worse than routine); 3 (acceptable, noisier than routine); 4 (good, same as routine), and 5 (excellent, better than routine).…”
Section: Methodsmentioning
confidence: 99%
“…Regions of interest were drawn to encompass the breast tissue, excluding the pectoralis muscle, with the average counts per pixel recorded. A reader also provided an overall assessment of diagnostic image quality and noise level as previously described [16] and an assessment of motion artifacts. Image quality was scored using the following 1-5 scale: 1 (poor, non-diagnostic); 2 (suboptimal, worse than routine); 3 (acceptable, noisier than routine); 4 (good, same as routine), and 5 (excellent, better than routine).…”
Section: Methodsmentioning
confidence: 99%
“…In the diagnostic setting, prior studies have shown similar sensitivities (> 90%) in patients recommended for biopsy [1,4,[14][15][16]. In recent years, several innovations in detector and collimator configuration of the direct-conversion molecular breast imaging system allow the same performance at a substantially lower dose of 99m Tc-sestamibi-300 MBq compared with 740-1100 MBq previously used [7,[17][18][19][20]. Because of the high sensitivity achieved at lower doses, combined with relatively high specificity, ranging from 86% to 94%, breast gamma imaging may be a valuable tool in the evaluation of breast cancer [8,18].…”
Section: Direct-conversion Molecular Breast Imagingmentioning
confidence: 95%
“…Molecular breast imaging usually refers to a configuration of two detectors made of a semiconductor cadmium zinc telluride that directly converts gamma ray energy into electronic signals [5]. The term "direct-conversion molecular breast imaging" has been introduced to specify the dualhead semiconductor configuration [6,7].Multiple possible uses for breast gamma imaging are being actively investigated, including screening [8,9], diagnostic problem solving [1,5], evaluation of extent of disease and contralateral screening for patients with newly diagnosed breast cancer [10][11][12], and prediction and evaluation of response to neoadjuvant chemotherapy [6,13]. In the screening setting, adjunctive molecular breast imaging in combination with…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Single-photon emission computed tomography (SPECT) represents one of the standard technologies for most nuclear medicine departments [7,8]. Recently, research has focused on radioiodinated and 99m Tc labeled radiopharmaceuticals for targeting solid tumor [9][10][11][12][13][14][15][16][17][18][19]. The introduction of new radiopharmaceuticals, which target specific receptor in solid tumor, could potentially have high tumor uptake and high solid tumor to normal muscle (T/NT) ratio which result in potential diagnostic radiopharmaceuticals with a high quality [20].…”
Section: Introductionmentioning
confidence: 99%